A taxonomic update 20 years after the book release “The amphibians and reptiles of a lowland forest reserve in Vietnam”- Ho Ke Go: implications for conservation - Ziegler, Thomas; Ong, An Vinh; Hoang, Quang Xuan; Pham, Cuong The; Nguyen, Truong Quang (Academia Journal of Biology, 2022)
We provide a taxonomic update of the herpetofauna of the Ke Go Nature Reserve, Ha Tinh province, north-central Vietnam, 20 years after the book release “The amphibians and reptiles of a lowland forest reserve in Vietnam”. In this work, Ziegler (2002) recorded 31 amphibians and 57 reptiles. Since then 30 changes in the generic assignment of species took place, five of six unnamed identifications could be solved, three unclear identifications clarified, and 12 taxa were newly described. This review has not only significance for updated names of taxa listed in the book and follow-up papers, but also for conservation. Reviews and descriptions resulted in taxa with more restricted distributions, such as, e.g., Gekko reevesii (formerly G. gekko, listed on CITES Appendix II and in the Red Data Book) and Pelodiscus variegatus (formerly P. sinensis, listed in the IUCN Red List, and split off taxa on CITES Appendix II). More species meanwhile are listed as threatened (in total 25), and for some of them, the threat status has increased in the meantime. In addition to the 88 amphibian and reptile species recorded by Ziegler (2002), three further records are added herein, resulting in 91 proven species. There is also evidence for the occurrence of 10 further reptile species, which would increase the herpetofauna list to 101. One half of these 10 additional reptile species are threatened which would increase the threatened herpetofauna to 30 species. This highlights the need for improved conservation, both concerning the official protection status of so far not yet officially listed threatened taxa and IUCN’s One Plan Approach conservation, covering in situ conservation measures and ex situ conservation breeding approaches. Representing one of Vietnam’s last remaining lowland forests with a high biodiversity and conservation value, the Ke Go Nature Reserve highly deserves reinforced conservation measures.